Detrimental changes to the health and well-being of healthcare workers in an Australian COVID-19 hospital - Joanne M Stubbs; Helen M Achat; Suzanne Schindeler (BMC, 2021)
Abstract Background Most studies examining the psychological impact of COVID-19 on healthcare workers (HCWs) have assessed well-being during the initial stages or the peak of the first wave of the pandemic. We aimed to measure the impact of COVID-19 and potential changes over time in its impact, on the health and well-being of HCWs in an Australian COVID-19 hospital. Methods An online questionnaire assessed current and retrospective physical and mental health; psychological distress (Kessler Psychological Distress Scale); lifestyle behaviours; and demographics, providing measures of health and wellbeing at three phases of the pandemic. Targeted staff were invited to participate via email and in-person. Additional promotional activities were directed to all staff. Changes in general health, mental health and psychological distress were examined using McNemar's Chi-square. Associations between other categorical variables were tested using Chi-Square or non-parametric equivalents as appropriate. Logistic regression explored risk factors for current distress. Results Four hundred thirty-three eligible HCWs answered all (74 %) or part of the questionnaire. Current self-rated health and mental health were significantly better than during the height of the pandemic, but had not returned to pre-pandemic levels. Psychological distress was significantly more common during the height of the pandemic (34.2 %) than currently (22.4 %), and during the height of the pandemic distress was significantly more common among younger than older HCWs. Females were significantly more likely to be distressed that males currently, but not during the height of the pandemic. High distress during the height of the pandemic was more likely to be maintained by HCWs who were less physically active than usual during the height of the pandemic (OR = 5.5); had low self-rated mental health before the pandemic (OR = 4.8); and who had 10 or more years of professional experience (OR = 3.9). Conclusions The adverse effects of the pandemic on HCWs have lessened with the easing of pandemic demands, but health and well-being have not reverted to pre-pandemic levels. This indicates continued exposure to elevated levels of stress and/or a sustained effect of earlier exposure. Initiatives that provide ongoing support beyond the pandemic are needed to ensure that HCWs remain physically and mentally healthy and are able to continue their invaluable work.